2022
DOI: 10.3390/ijms23137008
|View full text |Cite
|
Sign up to set email alerts
|

Pb-Induced Eryptosis May Provoke Thrombosis Prior to Hemolysis

Abstract: Lead (Pb) is a common metal, which can be toxic to the human body via the pollution of water or food, and can cause anemia and other diseases. However, what happens before hemolysis and anemia caused by Pb poisoning is unclear. Here, we demonstrated Pb can cause procoagulant activity of erythroid cells leading to thrombosis before hemolysis. In freshly isolated human erythroid cells, we observed that Pb resulted in hemolysis in both concentration- and time-dependent manners, but that no lysis occurred in Pb-ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…Thus, it can be postulated that eryptosis should be triggered by lower concentrations of xenobiotics compared with hemolysis. Indeed, xenobiotics-induced eryptosis is shown to precede hemolysis in multiple studies [44,[73][74][75][76][77]. This hypothesis is also supported by some nanotoxicological studies for Fe 3 O 4 magnetic NPs [44] or polyvinylpyrrolidone-and citrate-coated silver NPs [43].…”
Section: Discussionmentioning
confidence: 66%
“…Thus, it can be postulated that eryptosis should be triggered by lower concentrations of xenobiotics compared with hemolysis. Indeed, xenobiotics-induced eryptosis is shown to precede hemolysis in multiple studies [44,[73][74][75][76][77]. This hypothesis is also supported by some nanotoxicological studies for Fe 3 O 4 magnetic NPs [44] or polyvinylpyrrolidone-and citrate-coated silver NPs [43].…”
Section: Discussionmentioning
confidence: 66%
“…Since no evidence of etiology was found, the authors presumed that chronic lead exposure might be the reason of the thrombosis ( 18 ). Later in an experimental study, Jin et al demonstrated lead can cause reactive oxygen species -independent but [Ca 2+ ] i -dependent eryptosis, which might provoke thrombosis ( 19 ). However, to date, there have been no studies analyzing the relationship between the levels of lead in the blood and VTE.…”
Section: Introductionmentioning
confidence: 99%